SIMULATION OF HYDROLOGICAL SCENARIOS IN THE JAGUARI/RS RIVER WATER BASIN USING THE SWAT MODEL - Von Ende Dotto, Antônio; de Souza Robaina, Luís Eduardo; Trentin, Romário (Ra'e Ga: o Espaço Geográfico em Análise, 2024)
Hydrological models are computational tools that can assist in the management of river basins through modeling the water balance. This modeling allows for the predicting impacts caused by the uncertainty of the future climate that affects socioeconomic activities and environmental conditions. In this sense, this study applied the Soil and Water Assessment Tool (SWAT) model to simulate hydrological scenarios in the Jaguari River Basin. The simulation period carried out was determined based on the availability of data for modeling and validation. Therefore, in this context of data scarcity, the calibration period was from 2013 to 2016 and the validation period was from 2017 to 2019. The manual calibration method used ensured a coherent water balance in all simulated hydrological processes, achieving good results for flow, with an efficiency coefficient of 0.74 and correlation of 0.86 during calibration, and coefficients of 0.72 and 0.85 during validation. After adjusting the model, an alternative scenario was inserted, preserving the riparian forests of the Jaguari River Basin hydrographic network, resulting in notable changes, such as greater groundwater storage and increased flow due to the greater fraction of water in the base flow. The hydrological simulation demonstrated success, highlighting the modeling capacity even in the face of limitations in data acquisition at national level. It is recommended, in future work, to apply alternative scenarios of land use or climate change, taking advantage of the adjusted calibration obtained.